تأثير الصورة الإعلامية على الرأي العام - هدار خالد; هدار فضيلة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2022)
إن ما نشهده ونشاهده من موجة التطور التكنولوجي، وانتشار وسائل التواصل الاجتماعي وسط كل مجتمعات ، جعل بعض القيم؛ إن لم نقل معظمها، تتغير، وأصبح من يملك قوة هذه التكنولوجيا مهيمنا على العالم، وله القدرة في توجيه ثقافة القيم بما يخدم مصالحه، وتعتبر ثقافة الصورة أهم ما استغلوه وسعوا ولا زالوا يسعون للتحكم فيها وتوجيهها حسب هواهم، متناسين ما تتميز به الشعوب من خصوصيات. رغم هذه الخصوصية، إلا أن رواج عصر الصورة بإيجابياته وسلبياته جعلها تلقى صدى كبيرا لدى جمهورها، خاصة إذا اعتبرنا أن الصورة أشد صدقا من النصوص، فهي الأكثر استفزازا لفكر المشاهد والأوسع استحواذا على ذهنيته. لما أصبحت الصورة تستعمل لصناعة مفاهيم مقصودة، ونشر ثقافة محددة، أصبح لها تأثير على المعرفة، وتوجه الفرد وفق متطلباته باختلافها وبغض النظر عن سلامتها، عن طريق إثارة الاهتمامات حيال أحداث ومواضيع معينة، والمخاوف من أخرى، لتساهم في تغيير السلوك، وهيمنة ثقافة المظهر، مع بقاء جانب ايجابي للصورة ممثلا في الإبداع، والجمال، والدعوة. الكلمات المفتاحية: عصر الصورة، العولمة، ثقافة الصورة، الإعلام الجديد. Summary : Now, what we see from the technological development and the spread of social media around the world, made some values or most of it change, and whoever possesses the power of this technology has become dominant over the world. and has the ability to direct the culture of values to serve his interests and goals, and the culture of the image is considered the most important thing that they have exploited and sought and are still seeking to control and direct according to their whims, forgetting the peculiarities of peoples . Despite this peculiarity, the popularity of the image era, with its pros and cons, made it resonate with its audience, especially if we consider that the image is more honest than texts, as it is the most provocative to the viewer’s thought and the most dominant and possessive of his mentality. When the image is used to create intended concepts and spread a specific culture, it has an impact on knowledge, economics, and orientation of the individual according to his different requirements, regardless of their safety or not, by raising concerns about certain events and topics, and fears from others, to contribute to changing behavior. And the dominance of the culture of appearance, while remaining a positive aspect of the image represented in creativity, beauty, and advocacy.